Analisis Kesalahan Siswa Kelas Vii Smp Muhammadiyah 8 Surakarta Tahun Ajaran 2016/2017 Dalam Menyelesaikan Soal Operasi Hitung Aljabar - Maslakhah, Umi, Drs. Slamet.Hw (2017)
The purpose of research to describe the error students in the complete the operation of arithmetic algebra class VII and analyze factors students do the error. This research is descriptive qualitative. Subject research is 27 grade students VII C. junior Muhammadiyah 8 surakarta the school year 2016/2017. Data collection methods used in this study is a test, interviews, and documentation. Data analysis technique by reducing the data, the presentation of the data, and withdrawal conclusion. The results showed that the mistakes made students in the complete a matter of operation calculate alabar: (1) error in understanding the meaning of matter; (2) error in understanding and apply the concept; and (3) error in the calculation. Factors that cause students wrongdoing ie students don't understand with a view of the matter of a given students not master materials prerequisite, students less familiar with the material, students forget formula and basic concepts algebra, students less berlatihdalam menyelesiakan questions on the operating calculate algebra, students not careful in surgery count, students not checked re answers have done. Keywords: analysis, error students, operation of arithmetic algebra.